2016
DOI: 10.1055/s-0042-108647
|View full text |Cite
|
Sign up to set email alerts
|

STandardisierte BerichtsROutine für Sekundärdaten Analysen (STROSA) – ein konsentierter Berichtsstandard für Deutschland, Version 2

Abstract: Although secondary data analyses have been established in recent years in health research, explicit recommendations for standardized, transparent and complete reporting of secondary data analyses do not exist as yet. Therefore, between 2009 and 2014, a first proposal for a specific reporting standard for secondary data analysis was developed (STROSA 1). Parallel to this national process in Germany, an international reporting standard for routine data analysis was initiated in 2013 (RECORD). Nevertheless, becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(40 citation statements)
references
References 13 publications
0
31
0
9
Order By: Relevance
“…In 2014, the authors' working group was granted access to these quality assurance data. The current study was approved by the ethics committee of the Technical University of Munich and was performed according to the Good Practice of Secondary Data Analysis (GPS 12 ) guidelines and the recommendations for reporting observational studies conducted using routinely collected health data (STROBE and STROSA2 [13][14][15] ). Nonanonymous patient-level data hosted by the AQUA Institute were accessed in conformance with German data protection laws and controlled by AQUA Institute staff members (T.K., T.B.…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, the authors' working group was granted access to these quality assurance data. The current study was approved by the ethics committee of the Technical University of Munich and was performed according to the Good Practice of Secondary Data Analysis (GPS 12 ) guidelines and the recommendations for reporting observational studies conducted using routinely collected health data (STROBE and STROSA2 [13][14][15] ). Nonanonymous patient-level data hosted by the AQUA Institute were accessed in conformance with German data protection laws and controlled by AQUA Institute staff members (T.K., T.B.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was conducted according to Good Practice of Secondary Data Analysis guidelines 17 and reporting follows the STROSA2 guideline (modification of the RECORD guideline that addresses specific characteristics of the German healthcare system). 18,19 Data have been saved and are available on the GFSO servers. They were accessed using controlled remote data processing, which means individual patient data or institutional identifiers for hospitals were not available to the authors.…”
Section: Data Processing and Patient Flowmentioning
confidence: 99%
“…This study is reported in line with A Consensus German Reporting Standard for Secondary Data Analyses, Version 2 (STROSA) [9]. …”
Section: Methodsmentioning
confidence: 92%